USM EMPOWERS POSTGRADUATES’ POTENTIAL TO ORGANISE INTERNATIONAL LEVEL PROGRAMMES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 5 August 2015 – Universiti Sains Malaysia (USM) has always empowered the postgraduate students’ potential in organising programmes at the international level and this can be seen in the recent success of the 5 International Conference For Young Chemists (ICYC) 2015, which was fully organised by postgraduate students from the School of Chemical Sciences.